Optimization of the Characteristic of Hydroxyapatite Coating on Ti6Al4V Alloy by Electrophoretic Deposition - Ruaa A. Salman; Hussein A. Jaber; Wissam K. Hamdan (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
In this work, hydroxyapatite (HA) Nano-composite was applied as a coating layer on Ti-6Al-4V alloy by electrophoretic deposition and optimized according to the Taguchi approach. The effect of coating parameters, voltage (40, 60, and 80 V), time (2, 5, and 7 min), and concentrations (1, 2, and 3 g/L) was studied to optimize the quality of HA coating. The porosity, thickness, and Nano-roughness of HA coating layers were characterized by optical microscopy and atomic force microscope (AFM). Results disclosed that the amount of porosity in the coatings decreases from 21.52 % to 0 % as the concentration of HA particles, time of deposit, and voltage value increase. The thickness of HA coating increases as the deposit rate rises. The thickness of the coating prepared with conditions (80 V, 3 g/L, and 5min) is shown the higher value which is 18.304 μm with no observed porosity. The roughness of samples was measured only for the covered samples with a lesser amount of porosity. It is found that the highest Nano-roughness was obtained with sample 9 at 80 V, concentration 3 g/L, and time 5 min and it was 9.5263 nm.